Evaluation of age-friendly guidelines for public buses - Broome, K.; Worrall, L.; Fleming, J.; Boldy, Duncan (Pergamon, 2013)
Background - Older people commonly experience difficulty using public transport, and identify a range of barriers and facilitators to bus use. Purpose - This study aimed to evaluate the impact of implementing age-friendly guidelines for public buses on bus use, useability and social participation for older people. Methodology Age-friendly changes were implemented in Hervey Bay, Queensland, over a 3 year period. Changes included more lower floor buses, age-awareness training for bus drivers, more frequent scheduling, improved pedestrian infrastructure, a bus buddy program and trial of a flexible route bus. Brisbane, Queensland, served as a control site. This study adopted two complementary methodologies for evaluating the impact of age-friendly changes. The first study incorporated on-board satisfaction surveys with 335 bus users. The second involved a repeated measures cohort study (n = 100) with bus users and non-users.Results - Implementation of age-friendly changes in Hervey Bay, Queensland, resulted in improved satisfaction with, and perceived useability of, the bus system. Participants in Hervey Bay maintained their bus use and social activity participation, while participants in Brisbane experienced a decline in ease of bus use and social activity participation over the intervention period. Conclusion - The implementation of age-friendly guidelines for public buses may improve the useability of bus systems for older people and result in maintenance of participation in social activities.